Studies on Drag Reduction in Pipe Flow of Heavy Oil by Using Polymer Additives - Singh, Kamaljit (My University, 2019)
Some authors have observed that when a minute amount of high molecular weight polymer injected in the pipe flow, a significant amount of drag has been decreased. This phenomenon is known as drag reduction phenomenon. Although, the drag reduction by using polymer additives is quite effective still the design of the experimental set-ups and injection system is more complex. In this study, instead of using synthetic polymers, biopolymers like guar gum and gum Arabic were investigated in the one-phase and two-phase flows. Although some authors were able to produce the drag reduction percentage almost 80% with synthetic polymers using premixed solution. In this study, the biopolymers were tested in the turbulent flow and heterogeneous injection of the polymers was used. With heterogeneous injections using biopolymer additives almost 70% drag reduction was observed. Moreover, guar gum and gum arabic are easily available and quite cost effect than synthetic polymers. These both biopolymers are environment friendly because of non-toxic in nature and easily bio-degradable. The other favorable properties of guar gum and gum arabic are gel and film forming ability, higher viscosity and high ability for chemical modification and cross linking. In the earlier experimentation, the experimental set-up was designed for the injection of the polymer solutions near the boundary layer. By performing some pilot experiments three polymers were selected. One was oil-soluble polymer known as polydimethylsiloxane and the other two polymers were water-soluble polymers i.e. guar gum and gum Arabic. Guar gum is easily soluble in water to produce highly viscous solution, while on the other side gum arabic is also readily soluble in water but do not form too viscous solution like guar gum. However, if allow hydration overnight, the solubility is enhanced. Rheological characterization of the selected polymers was done. The effect of the polymer concentration and the shear rate on viscosity was observed. It was observed that with the addition of the polymers there was an increase in the viscosity of the solvent. The increase in the viscosity of the solution was more rapid in the case of guar gum as compared to gum Arabic and polydimethylsiloxane. Even at the low concentration guar gum was able to increase the viscosity of the solvent 500 times with 3000 ppm of the concentration. The effect of the shear rate was observed on the viscosity of the polymer solutions. It was found that with an increase in rate there was a decrease in the viscosity of the guar gum and gum arabic solutions. For guar gum, the behavior of the solution for all the concentrations was shear thinning behavior. For gum arabic, the behavior of the solution for higher concentrations was found to be shear thinning, but for lower concentrations, there was Newtonian behavior was observed. For the polydimethylsiloxane, the Newtonian behavior was observed in case of all the concentrations. In rheological characterization, the effect of the temperature was observed from 25 oC to 45 oC on polymer solution viscosity and density. It was found that with an increase in the temperature, the viscosity of the solution decreases and the same was observed in the case of density for selected polymers. The density of the water was not affected by the addition of the polymer concentration but increased with the addition of the KCl salt concentration. For polydimethylsiloxane, there was an increase in the viscosity of the polymer solution with an increase in concentration and the density of the solution decrease considerably with increase in temperature. After rheological characterization, the selected polymers were tested in the one-phase flow. The effect of the Reynolds number and concentration of the polymer was investigated on drag reduction percentage. It was observed that the 71.4% drag reduction was observed with guar gum solution and 62.1% maximum drag reduction was observed with gum Arabic solution. The degradation of the polymer solutions was studied under the high shear conditions and the effect was continuously observed with a number of passes in a closed system. The shear stability of both water-soluble polymers was improved with the addition of the KCl salt and optimum concentration was selected. Then polydimethylsiloxane, an oil-soluble polymer was tested in the turbulent condition to investigate the effect of the concentration on the drag reduction percentage. The maximum drag reduction with the oil-soluble polymer was observed to be 23.9%. since the viscosity of the oil was high so it was not easy to maintain the high Reynolds number. Also, the effect of the slot injection was studied with and without perforated end. It was found that the perforated end was able to produce more drag reduction effect than the injection end without perforation. The selected polymers were also tested in the two-phase flow system. Since the water-soluble polymer was quite effective in one phase flow then a further study has been done by using similar water-soluble polymers in two-phase flow systems. Water and oil flow simultaneously in the pipe and the water-soluble polymer was injected in the water flow. The mixing of the water and oil was done by using’ the Y’ junction at the entrance. Both the polymers also produced a positive effect in the two-phase flow system. The effect of the polymer concentration, mixture velocity and oil fraction on the drag reduction was observed. The effect of the polymer was maximum at 0.1 oil fraction, and then considerable drag reduction effect was observed up to 0.3, thereafter, a decrease in the drag reduction percentage was observed up to 0.5 fraction. The minimum drag reduction effect was observed at 0.7 fraction of oil which eliminates with further increase in the fractions of oil. Simultaneously, the study of the flow patterns was also observed in two-phase flow systems and the effect of the polymer concentration on the flow patterns was recorded in the form of photographs. It was found that there was an increase in the stratification of the flow with the addition of the polymer in the water/oil flow systems. A problem was found with the master polymer solutions, that there was a decrease in the effectiveness of the polymers after 3 number of days. So, the stability study was done to maximize the stability and to observed the effect of the polymer concentration on the stability of the master solution. The polymers were added in the different concentration and the stability was checked with number of days. It was found that the guar gum solution was more stable than the gum arabic solution. If the guar gum solution can be changed to a hydrogel, the solution can be stable up to 15 days with negligible degradation.
Keywords: Drag reduction; Biopolymers; Rheology; Single-phase flow; Two-phase flow; stability